Experimental chatter characterization in metal band sawing - Thaler, Tilen (Strojniški vestnik, 2014)
One of the most detrimental instability phenomena in metal band sawing is chatter, i.e. high amplitude vibrations of the tool and/or workpiece. In this paper, the influence of the cutting speed and of the distance between the blade supports on chatter phenomena is investigated. For this purpose a series of experiments with triangular cutting speed variation at several pre-selected distances between the blade supports was conducted on structural steel (St37, DIN 17100) workpieces. A feature for chatter detection was extracted from the power spectra of the machine vibration signal, and a set of characteristics was introduced for experimental chatter characterization. The results showed the presence of a chatter hysteresis which depended on the cutting speed. Additionally, apart from the blade support distance, the cutting speed was shown to be a strongly influencing parameter, and as such also promising for chatter control in band sawing processes
Keywords: drdranje; empirična karakterizacija; histereza; hysteresis; nestabilnost procesov; spektralne analize; tračno žaganje